[2026-08-24] Knowledge, Attitudes, and Practices Regarding Patient Safety Incident Reporting Among Tertiary Hospital Healthcare Workers: A Cross-Sectional Study - Nguyen Thi Quy; Hoang Xuan Quynh; Hoang Thi Ngoc Sen (Research Medical Journal, 2026)
Background: Patient safety incident reporting is a critical component of patient safety systems; however, underreporting remains a persistent challenge in many healthcare settings. Although the knowledge and attitudes of healthcare workers toward reporting are studied, their relationship with actual reporting practices remains unclear. Objectives: To describe knowledge, attitudes, and practices (KAP) regarding patient safety incident reporting, and to investigate factors associated with reporting practices among healthcare workers in a tertiary hospital in Vietnam. Methods: This cross-sectional study involving 280 healthcare workers was conducted in a tertiary hospital in Vietnam. A structured questionnaire assessing KAP related to patient safety incident reporting was used to collect; practice was evaluated only among participants with prior reporting experience. Participant characteristics and KAP levels were summarized using descriptive statistics. Spearman correlation was used to examine the relationships between continuous variables and practice scores, whereas chi-square or Fisher exact tests were used to assess the associations between categorical variables and reporting practices. Results: Of the 280 participants, 41.1% demonstrated good knowledge and 84.6% showed positive attitudes toward patient safety incident reporting, with only 51.1% having ever reported a patient safety incident. Among the 143 participants with reporting experience, 61.5% demonstrated appropriate reporting practices. No significant associations were found between reporting practices and age, work experience, knowledge, or attitudes (P > .05). Gender was the only factor that was significantly associated with reporting practices (P = .04). Conclusions: Despite having positive attitudes, knowledge gaps and suboptimal reporting practices persist among healthcare workers. The lack of association between knowledge, attitudes, and reporting practices suggests that system-level factors play a more important role than individual awareness. Interventions should focus on improving practical training, strengthening reporting systems, and fostering a nonpunitive reporting culture to enhance patient safety.